What you see is not what you get: a case of the quality of services - Ibn Usman, Muhammad Awwal; Mohd Ali, Hairuddin (IIUM Press, 2011)
A brief investigation of quality services in one of the kulliyyahs in IIUM. The study was based on the SERVQUAL framework. The study managed to highlight some of the service aspects that needs to be improved for customer satisfaction.